1994
DOI: 10.1063/1.466972
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics study of the curvature correction to the surface tension

Abstract: The first order curvature correction to the surface tension of a drop is given by Tolman’s length. Up until now, no accurate estimates of this length existed for realistic fluids. Recently Blokhuis and Bedeaux proposed a new relation that expresses Tolman’s length as an integral over the pair distribution function of a planar liquid–vapor interface. We have used this relation to obtain estimates of Tolman’s length from molecular dynamics simulations of a Lennard-Jones liquid–vapor interface. We found it to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
2
3

Year Published

2001
2001
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(95 citation statements)
references
References 13 publications
10
80
2
3
Order By: Relevance
“…In practice, however, only the mechanical surface tension ͑␥͒ can be measured directly either from experiments 43 or from computer simulations. 44 In the absence of an external electric field, the measured surface tension ␥ is essentially the same as the thermodynamic surface tension , which is independent of the location of the dividing surface. In the presence of the field, the measured surface tension ␥ will in principle depend on the location of the dividing surface.…”
Section: ͑40͒mentioning
confidence: 72%
“…In practice, however, only the mechanical surface tension ͑␥͒ can be measured directly either from experiments 43 or from computer simulations. 44 In the absence of an external electric field, the measured surface tension ␥ is essentially the same as the thermodynamic surface tension , which is independent of the location of the dividing surface. In the presence of the field, the measured surface tension ␥ will in principle depend on the location of the dividing surface.…”
Section: ͑40͒mentioning
confidence: 72%
“…Calculations from DFT have always resulted in a negative Tolman length, [4][5][6][7][8] while results from simulations have resulted in a positive Tolman length. [9][10][11] These simulations have always been of a planar interface, taking advantage of the limit of infinite droplet size in order to determine the Tolman length. In this work, we focus instead on simulations of liquid droplets and determine the Tolman length from the Laplace equation, specifically, the dependence of the different in bulk pressures on the curvature.…”
Section: Discussionmentioning
confidence: 99%
“…3 Theoretical estimates using density functional theory ͑DFT͒ result in negative values for the Tolman length, [4][5][6][7][8] while computer simulations of planar interfaces give positive values for the Tolman length, via Eq. ͑6͒ below, [9][10][11] or were inconclusive. 12, 13 Moody and Attard 14 determined the Tolman length from simulations of a liquid near coexistence solvating a hard-wall cavity and found that the Tolman length was positive at low temperatures, changed sign at a certain temperature, and became increasingly negative as the temperature increased.…”
Section: Introductionmentioning
confidence: 99%
“…͑7͒ and noting that dR n ϭ0 ͑for fixed solid-particle size͒, V 2 dp 2 ϭN 2 d ͑or dp 2 ϭ 2 d ͒ and V 1 dp 1 ϭN 1 d ͑or dp The generalized Laplace equation ͑5͒ and generalized Gibbs-Duhem equations ͑10͒ and ͑11͒ are key thermodynamic equations for the study of heterogeneous nucleation. We note that in our consideration 32 and 21 in these equations depend only on the curvature of the droplet, but not on the thickness of the liquid film. Only ˜(R n ϩh) in Eq.…”
Section: Thermodynamics Of Heterogeneous Nucleationmentioning
confidence: 99%
“…͑24͒ can be determined from the DFT, 32 , 21 , and h on the right-hand side are strongly dependent on the choice of the dividing surface. For the liquid-vapor interface, we have chosen the equimolar dividing surface as the dividing surface so that ⌫ 21 ϭ0.…”
Section: ͑24͒mentioning
confidence: 99%